Status quo, influencing factors, and association with hospitalization outcomes of malnutrition in neurological disorders in China: a national cross-sectional study - Lan, Lan; Guo, Shuyan; Han, Yujia; Zhai, Shuo; Liu, Yan; Li, Pengfei; Zhang, Xudong; Dong, Siping (Frontiers in Nutrition, 2025)
BackgroundIn recent years, the issue of malnutrition in people with neurological disorders has emerged as a growing concern. However, there is still a lack of global research on the current status of malnutrition in these disorders in China, which warrants further investigation. This study aims to clarify the prevalence of malnutrition in these disorders, evaluate its contributing factors, and assess its impact on hospitalization outcomes.MethodBased on the China Nutrition Fundamental Data 2020 (CNFD 2020) Project, this nationwide survey was conducted from February to October 2023 across 31 provincial-level administrative regions of China, utilizing questionnaires for data collection. The study included 1,357 patients with neurological diseases, whose nutritional status was systematically assessed using the standardized Global Leadership Initiative on Malnutrition (GLIM) diagnostic framework. Statistical analyses were performed using descriptive statistics, multivariate logistic regression, random forest, Kruskal-Wallis test and multiple linear regression.ResultsThe overall prevalence of malnutrition in patients with neurological disorders was 32.5%, including 30.8% moderate malnutrition and 1.7% severe malnutrition. Multivariate logistic regression identified neutrophil percentage (OR = 1.026, P < 0.001, 95%CI: 1.015–1.038) and western region (OR = 1.319, P < 0.001, 95%CI: 1.002–1.734) as significant influencing factors for malnutrition. Random forest analysis showed that lymphocyte percentage, red blood cell count and education level ranked highest in SHapley Additive exPlanations (SHAP) values. Boxplot analysis demonstrated that malnutrition status may increase both length of stay and hospitalization costs.ConclusionsMalnutrition is prevalent in patients with neurological disorders, with neutrophil percentage, lymphocyte percentage, red blood cell count, region, and education level identified as significant contributing factors. Malnutrition may be associated with increased length of stay and hospitalization costs.